2006
DOI: 10.1002/cphc.200600300
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding Polyelectrolyte Films as Sensors for Osmotic Pressure

Abstract: Freestanding ultrathin polyelectrolyte-multilayer membranes, transferred to topographically structured polydimethylsiloxane (PDMS), are used as mechanical sensors. Due to the membranes' semipermeability, high-molecular-weight molecules can be either entrapped inside them or excluded, thus generating an osmotic pressure. This leads to a deformation. We investigate the deformation as a function of the osmotic pressure and present an analytical theory that fully describes the data. Thus, osmotic pressures can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Semipermeable and pliable polyelectrolyte multilayers suspended over pores or cavities have been investigated for the development of micromechanical devices, sensors, and separation/filtration membranes 2,11,25,29,30,37. Several past studies have demonstrated that suspended PEMs can be created by transferring freestanding PEMs onto substrates containing holes, cavities, or pores 2,25,29,30,37.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semipermeable and pliable polyelectrolyte multilayers suspended over pores or cavities have been investigated for the development of micromechanical devices, sensors, and separation/filtration membranes 2,11,25,29,30,37. Several past studies have demonstrated that suspended PEMs can be created by transferring freestanding PEMs onto substrates containing holes, cavities, or pores 2,25,29,30,37.…”
Section: Resultsmentioning
confidence: 99%
“…Several past studies have demonstrated that suspended PEMs can be created by transferring freestanding PEMs onto substrates containing holes, cavities, or pores 2,25,29,30,37. To determine whether our freestanding PEI/PVDMA multilayers could be transferred onto other substrates and suspended across holes or pores, we fabricated 100-bilayer freestanding films and treated the films with the amine-functionalized fluorophore tetramethylrhodamine cadaverine (TMR).…”
Section: Resultsmentioning
confidence: 99%
“…[98,99] Several other methods, relying on different physical principles, are well suited to characterizing thin films, some of them in a liquid state. These include quartz crystal microbalance, [50,100] piezo-rheometry, [101] resonance frequency, [102] bulging tests, [103] the pendant drop technique, [104] osmotic pressure, [105] or the capillary wave technique [106] in the case of free-standing films. The stiffness of PEM can be modulated from a few kPa to several GPa depending on the structural properties of the polyelectrolytes, but also on the degree of cross-linking inside the film.…”
Section: Modulation Of Mechanical Propertiesmentioning
confidence: 99%
“…This aspect provides a robust, stable surface ideal for patterning, functionalization, and harsh characterization procedures; however, there can also be eminent value in detaching these coatings. Ultrathin polymer films have been a prevalent field of study for practical interests concerning microfluidics, ultrafine filtration, and microelectronics . Common preparation techniques include layer‐by‐layer (LbL), Langmuir‐Blodgett, self‐assembly, and cast films .…”
Section: Detached Polymer Filmsmentioning
confidence: 99%
“…Ultrathin polymer films have been a prevalent field of study for practical interests concerning microfluidics, ultrafine filtration, and microelectronics. [111][112][113] Common preparation techniques include layer-by-layer (LbL), 114,115 Langmuir-Blodgett, 116 self-assembly, 117 and cast films. 118 However, recent studies have shown detaching polymer brushes to be a means that can offer control and tunability.…”
Section: Detached Polymer Filmsmentioning
confidence: 99%